O etiki in o njenem prevajanju v jezik književnosti - Verč, Ivan (Primerjalna književnost, 2006)
In literature the ethical act manifests itself as a conflict with the limits of the discursivity of language or with the possibilities that language offers in the process of verbalizing reality. Possibility requires choice, and for the subject of the creative verbal process the choice is the act of verbalization. The specifics of its occurrence have especially been described by the "hard" literary studies of the 20th century. Rather than the meta-ethical "translation" of theoretical and philosophical conceptions in the language of literature, it is therefore possible to speak of the independent ethical choice of being in the word. Literature has shown the path to the ethics of verbalizing reality much more than other categories of the humanities.
Keywords: književnost; literature; ethics; etika